Analysis Of Emotional Intelligence For Lecturers Of Management Study Program In IIB Darmajaya - Betty Magdalena; Linda Septarina; Besti Lilyana; Suwandi Suwandi (Prosiding International conference on Information Technology and Business (ICITB), 2021)
In academics, lecturers who have good emotional intelligence and good service to students can do something good in their work situations. In dealing with dailywork routines, a lecturer must be able to perform well in harmony with the Tri Dharma of Higher Education. The purpose of this study was to analyze the emotional intelligence of lecturers in Management study program, Institute of Informatics and Business Darmajaya. The method in this study used descriptive quantitative with a sample of 42 lecturers of the management study program. The results of this studyindicate that the emotional intelligence in Management study program, Institute of Informatics and Business Darmajaya had an average score range of 151.9. It was in the vulnerable range of values 145.8 - 179.4 in the high category. It showed that thecomponent of emotional intelligence, namely self-awareness: being able to introspect oneself well into the high category. in Management study program, Institute of Informatics and Business Darmajaya who were committed to their work in intelligent emotions, for those who were emotionally intelligent was able to motivate themselves, motivate others and control their emotions, for those who have insight when making decisions, for those who empathize with understanding thepsychology of others and build and maintain good social relations.Keywords—Emotional Intelligence, Lecturer